Enhancing Ecopreneurship Competency Through Bidan Elok E-Learning Based on Local Wisdom - Haris, Risma; Duygulu, Sergul; Hafidah, Andi; Syakur, Rosdiana; Djatmiko, Budi; Maryam, Andi; Indrawati, Andi (Aptisi Transactions On Technopreneurship (ATT), 2025)
Local wisdom-based ecopreneurship focuses on sustainability and environmental preservation, offering midwives the opportunity to utilize local natural resources efficiently while preserving social and cultural values. In South Sulawesi, integrating ecopreneurship into midwifery education remains underexplored. This study evaluates the effectiveness of the "Bidan Elok" E-Learning platform in enhancing midwifery students ecopreneurship competency, aligning with Sustainable Development Goals (SDGs) 4 (Quality Education) and 8 (Decent Work and Economic Growth). A One Group Pre-Test and Post-Test design was conducted with 150 midwifery students from Gowa, Makassar, Parepare, and Palopo. The study measured competency changes before and after using local wisdom-based learning media. Results indicated a significant improvement, with average scores increasing from 58.4 (pre-test) to 82.6 (post-test). Effectiveness varied by work experience, with the highest N-Gain score (0.72) in the 0-5 years experience group and the lowest (0.60) in the 15-20 years group. E-Learning media integrated with local wisdom values effectively enhanced students ecopreneurship competency. However, more adaptive approaches are needed for students with longer work experience. This study recommends further development of technology and culture-based learning methods to strengthen ecopreneurship competency in midwifery education and support SDG achievement.